The effects of cultural values on traditional Islamic - Arabic houses in the Middle East / Dana K. Amro and Azizi Bahauddin - Amro, Dana K.; Bahauddin, Azizi (Division of Research and Industry Linkages, UiTM Melaka, 2014)
Culture and design determine the space influenced values; they specifically outline space variations between values within a culture in relation to design space influenced values. By the vision of an ideal life, one can shape and mold the vision of space by reflecting cultural forces such as religious he liefs. The purpose of this study will determine cultural values and religious beliefs. In tum, assess the. effects on the formation ofhouses in the Middle East For this principle, the elements of traditional Islamic-Arabic homes showed effects by determining certain elements such as the bent entrance, the courtyard, Haramlak-Selamlak (women - men's quarters) and the Mashrabiyyah (wooden windows). Qualitative analysis was used as the method to analyze the case studies comparing traditional courtyard homes to today's housing. The results have shown that today's housing was unsuccessful when trying to imitate the provision of privacy as it was in the houses during the past.